Licensed larceny : infrastructure, financial extraction and the global south - Hildyard, Nicholas (Manchester capitalism, 2016)
Inequality is not just a problem of poverty and the poor; it is as much a problem of wealth and the wealthy. The provision of public services is one area which is increasingly being reconfigured to extract wealth upward to the 1%, notably through so-called Public Private Partnerships (PPPs). The push for PPPs is not about building infrastructure for the benefit of society but about constructing new subsidies that benefit the already wealthy. In other words, it is less about financing development than developing finance. Understanding and exposing these processes is essential if inequality is to be challenged. But equally important is the need for critical reflection on how the wealthy are getting away with it. What does the wealth gap suggest about the need for new forms of organising by those who would resist elite power?